A cross sectional study on health seeking behavior of migrant workers: Bangalore city - ., Shwetha; Prasad, K. N. (International Journal Of Community Medicine And Public Health, 2018)
Background: Global migrant population is 214 million people, which accounts for approximately 3% of world population.As per 2001 census 307.2 million people, which is 30% population in India were migrants as reported by place of birth, of which 42.1 million were interstate migrants in India. Migrant populations as being a non-native population, are vulnerable and are exposed to many health problems. Most of the health problems of migrants are ascribed to their migration to urban areas, decreased awareness about local health facility, inability to cope with psychological stress, unhealthy sexual practices, and frequent travelling. The objective of the study was to assess the health seeking behavior of the migrant worker in Bengaluru. Methods: This is a cross sectional, exploratory and community based study. The study was conducted in the field practice area of department of Community Medicine of Dr. B. R. Ambedkar Medical College and Hospital, Bengaluru. Total study subjects were 295 were selected by convenient sampling method. The study was conducted between May 2017 to June 2017. Data regarding health seeking behaviour was collected using semi structured questionnaire. Results: Migrants were from different states of our country. 25.7% were from other districts of Karnataka, 58.3% of them belonged to high risk occupation and 41.7% to low risk. Around 85% of the migrants discussed their health problem, 59% of them preferred home remedy as a first priority for their illness & 41% preferred private hospitals for major illness. Around 52.9% of study subjects waited for more than 3days before seeking health care. Conclusions: The health seeking behaviour was poor and delay in seeking healthcare during their illness.